Teaching biathletes the rules of shooting using electronic devices - Astafev, N.; Kukleva, G. (BIO Web of Conferences, 2020)
An advanced direction in marksmanship training of biathletes is teaching the rules of shooting: «marking» of a shot; defining the mean point of impact; correcting the sight; offset shooting. Teaching the rules of shooting using electronic devices will help to achieve the aim without a coach and will help to save cartridges. The article presents the description of the teaching programs algorythms for electronic devices.